Evidence of a Role for Aerobic Bacteria in High Magnesium Carbonate Formation in the Evaporitic Environment of Dohat Faishakh Sabkha in Qatar - Al Disi, Zulfa Ali; Jaoua, Samir; Bontognali, Tomaso R. R.; Attia, Essam S. M.; Al-Kuwari, Hamad A. Al Saad; Zouari, Nabil (Frontiers in Environmental Science, 2017)
Dolomite (MgCa(CO3)2) is an important petroleum reservoir rock mineral common in ancient sedimentary rocks which is infrequently found in modern environments. The mechanism of dolomite formation remains poorly understood, although recent research has focused on the contribution of microbial processes. Sabkha is the Arabic term for saline mudflats occurring in regions characterized by extreme environmental conditions (high temperature, salinity, light intensity, and aridity), where diverse halophilic and extremophilic microorganisms are found. The dynamic evaporitic systems characteristic of sabkhas are crucial for the precipitation of minerals and a role for microorganisms in sabkhas in the process of mineralization has been proposed. In this study the Dohat Faishakh Sabkha in Qatar was investigated for evidence of the role for aerobic bacteria in mediating the formation of high magnesium carbonates and dolomite, two minerals that commonly occur in the sabkha sediments. 29 strains of aerobic microbes were obtained through inoculation on agar plates from two different cores sampled from the sabkha and identified by 16S rRNA gene sequencing as belonging to the genera Bacillus, Salinivibrio, Staphylococcus and, primarily, Virgibacillus. All strains examined caused the pH of an artificial growth medium to increase from 7 to 8.5; however, not all were capable of mediating mineral formation. Only Salinivibrio and Virgibacillus spp. isolates mediated the formation of detectable solid phases within the agar plates. Light microscopy, scanning electron microscopy energy dispersive X-ray (SEM/EDX), and X-ray diffraction (XRD) analyses indicate that the solid phase produced in the presence of these bacterial strains is MgCa(CO3)2 with a MgCO3 mol% varying from 0% to 40%. The results of these laboratory experiments suggested that, in the Dohat Faishakh Sabkha, aerobic bacteria may contribute in the formation of very high Mg calcite, a mineral that is considered the precursor of ordered dolomite.